Development of Nanocapsules Containing Cytotoxic Agents- A Review: Kajian Literatur Pengembangan Sediaan Nanokapsul Mengandung Agen Sitotoksik - Priani, Sani Ega; Setianty, Tia Nur; Aryani, Ratih; Fitrianingsih, Sri Peni; Syafnir, Livia (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Background: The incidence and mortality of cancer are rapidly growing worldwide. Modification on drug delivery systems based on nanotechnology was applied to improve the effectiveness and safety of treatment. Nanoencapsulation, a part of nanotechnology, was known can be involved in cytotoxic agents. Objective: This research was conducted to determine the type of polymers for nanoencapsulation of cytotoxic agents and analyze the effect of nanoencapsulation on the cytotoxic activity. Methods: The study was performed by systematic literature review using selected articles from reputable databases that meet the inclusion and exclusion criteria. Results: The results show that many cytotoxic agents have been developed in nanocapsules systems due to their low water solubility, chemical instability, and low bioavailability. The nanoencapsulation process was carried out using synthetic or natural polymers such as polylactic-co-glycolic acid (PLGA), PEGylated PLGA, polycaprolactone (PCL), chitosan-sodium tripolyphosphate, chitosan-sodium alginate, heparin-poly(l-lysine), and polymethyl methacrylate (PMMA). Those polymers are widely used for nanoencapsulation related to their biocompatible, biodegradable, non-toxic, and providing the desired coating properties. The nanoencapsulation on cytotoxic agents significantly increases the in vitro cytotoxicity, marked by the decrease of IC50 value in the range 1.4-15.4 folds compared to pure drugs. The increase in cytotoxicity could be caused by particle size reduction, modification of particle surface properties, and enhancement of drug stability. Conclusion: It can be concluded that nanoencapsulation can be applied for cytotoxic agents to increase their activity using the appropriate coating polymer.